A Community Engagement Model for Improving Teachers’ Competence in Developing Sundanese Instructional Materials in Primary Schools - Yudhie Suchyadi; Rini Sri Indriani; Nita Karmila; Resy A. Ghani (Universitas Pakuan, 2026)
.